Effect of extenders and sperm concentration on migration efficiency of Malabari buck spermatozoa in bovine cervical mucus - S. Urmila; K. Lekshmi Bhai; B. Bibin Becha; C. Jayakumar; P.D. Divya (Journal of Veterinary and Animal Sciences, 2023)
The study evaluated the effect of extenders and sperm concentration on the migration efficiency of Malabari buck spermatozoa in bovine cervical mucus. Fresh semen ejaculates collected on six different days from three adult healthy Malabari bucks were pooled and divided into four groups based on the extender used (tris-egg yolk-based or liposome-based extender) and rate of extension (200 or 400 million motile spermatozoa per 0.5 mL) (n=6 per group) and subjected to cryopreservation. After freezing and thawing, Malabari buck spermatozoa cryopreserved in liposome-based extender travelled significantly (p<0.05) greater distance in bovine cervical mucus compared to those preserved in tris-egg yolk-based extender when packed in French medium straws with 200 million progressively motile spermatozoa. The corresponding values with 400 million progressively motile spermatozoa also showed the same trend. It was also observed that Malabari buck semen extended with 200 million progressively motile spermatozoa was significantly (p<0.05) better in terms of migration efficiency in bovine cervical mucus compared to that with 400 million progressively motile spermatozoa in both the extenders.